Magnetic resonance of the heart and great vessels : clinical applications - Bogaert, J; Duerinckx, André J; Rademakers, Frank E (Springer, 2000)
Magnetic resonance imaging is rapidly becoming a preferred noninvasive imaging modality for the heart and great vessels. This book is specifically designed to meet the needs of the general radiologist as well as clinicians (in particular cardiologists and cardiac surgeons) who are interested in the potential value of the technique. For those unfamiliar with the topic, a lucid description of the more essential features is included (e.g., normal anatomy, cardiac imaging planes, cardiac magnetic resonance sequences). Thereafter a comprehensive overview of clinical applications is provided by recognized authorities in the field, addressing both the strenghts and the current limitations of the technique in the assessment of cardiovascular disease.
Diagnostic imaging and radiation oncology
Medical radiology
Keywords: kardiovaskulární nemoci; chemie, klinická chemie; Blood Vessels; magnetická rezonanční tomografie; angiologie; Heart; Cardiovascular Diseases; Magnetic Resonance Imaging; srdce; cévy; kardiologie